(untitled) (The Geographic Base, 2019)
Abundance of female workers in tea estate is common phenomena in the context of Nepalese tea industry. Women are main work force especially for leaf picking in any tea industry. So, the role of women participation is notable in this sector. This study focusses on socioeconomic background of women workers in Guranse Tea Estate, Dhankuta. Both qualitative and quantitative methods have been used to collect data and information through questionnaire, interview, focused group discussion, key informant interview and observation. Various types and nature of tea workers are found in the tea industry. Different types of socio-economic background such as caste/ethnicity, age group, educational status, land ownership, income level etc. have been found in this tea estate. Most of the workers are represented from indigenous and ethnic group with 20-40 age group. Similarly, a large number of tea workers are illiterate and landless as well as having low level of income.